TB SKIN TEST RESPONSE IN CHILDREN WITH HIV INFECTION - N. I. Klevno (Туберкулез и болезни лёгких)
The paper presents the results of tuberculin and recombinant tuberculosis allergen (diaskintest) skin tests in HIV-infected children with tuberculosis. In general, the conducted investigations have shown that the tuberculin tests are of definite value in diagnosing tuberculosis in HIV-infected children. However, the lower the blood CD4 lymphocyte count, the less frequently the positive skin tests were recorded: the rate of recorded positive tuberculin tests was nearly 20% in patients with CD4 counts less than 200 cells/µl and it approximated those (within 85%) in non-HIV-infected patients with CD4 counts more than 500 cells/µl. The susceptibility to the diaskintest also decreased as immunodeficiency increased and it was comparable to that of the tuberculin test.